2020
DOI: 10.3390/ma13051085
|View full text |Cite
|
Sign up to set email alerts
|

Design and Mechanical Characterization of Voronoi Structures Manufactured by Indirect Additive Manufacturing

Abstract: Additive manufacturing (AM) is a production process for the fabrication of three-dimensional items characterized by complex geometries. Several technologies employ a localized melting of metal dust through the application of focused energy sources, such as lasers or electron beams, on a powder bed. Despite the high potential of AM, numerous burdens afflict this production technology; for example, the few materials available, thermal stress due to the focused thermal source, low surface finishing, anisotropic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…However, for anisotropic structures such as RV10 and RV30, it is meaningless to discuss the influence of the number of seed points on the effective thermal conductivity, because the orientation of the structure is also one of the main factors affecting its effective thermal conductivity. While existing studies have shown that the PPI is inseparable from the mechanical properties of the random Voronoi structure, especially the energy absorption capacity [ 25 ]. As has been mentioned above, the effective thermal conductivity of the structure is inversely proportional to the porosity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for anisotropic structures such as RV10 and RV30, it is meaningless to discuss the influence of the number of seed points on the effective thermal conductivity, because the orientation of the structure is also one of the main factors affecting its effective thermal conductivity. While existing studies have shown that the PPI is inseparable from the mechanical properties of the random Voronoi structure, especially the energy absorption capacity [ 25 ]. As has been mentioned above, the effective thermal conductivity of the structure is inversely proportional to the porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Nie et al [ 24 ] investigated the pressure drop of open-cell foams created by LVT with various pore densities and porosities. Almonti et al [ 25 ] proposed an indirect additive manufacturing method that combined the AM with metal casting to fabricate the open-cell foams designed by Voronoi tessellation and compared the resulting mechanical properties with commercial metal foams. These studies revealed that the porosity and pore size are significant structural parameters that are closely related to the property of the open-cell foam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples produced were characterized by different PPI values and branches thickness (r) as showed in Table 1; also, two different kinds of edges (smooth/regular) were considered. The structure of the samples was designed with the ad hoc method described in references [41,42]. A Spatial Voronoi Tessellation with the Rhinoceros plug-in GrassHopper was used to design the structure.…”
Section: Methodsmentioning
confidence: 99%
“…Almonti et al produced a foam structure made of a foundry resin using a 3D stereolithography laser printer. Following, this model was reproduced with a casting process to achieve a metal foam with the designed structure [41,42].…”
Section: Introductionmentioning
confidence: 99%